Special Education Integration Program (PPKI) Teachers: Task Load And Job Satisfaction - Nordin, Mohd Norazmi bin; Mustafa2, Mohamad Zaid Bin; Razzaq, Abdul Rasid Bin Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The task loads has long been an issue among teachers in Malaysia. These expenses increase to teachers for the Special Education Integration Program (PPKI). This high burden of duty will undermine the PPKI teachers’ job satisfaction. Although there are many studies on this issue in Malaysia and abroad, however, specific studies on the impact of the task load on the job satisfaction of special education teachers in Malaysia are still being ignored. Therefore, following the continuation of the issue, this qualitative study is aimed for exploring the elements of PPKI task load constructs that influences PPKI teacher job satisfaction in Johor, Malaysia. This study uses the full range of interview methods in collecting data. Interview sessions were administered to 11 coordinators of PPKI for each district in Johor. Thematic analysis was conducted based on the transcript of the interview that has been produced. The findings show there are five elements of PPKI teacher task loads in Johor namely time, type of assignment, working environment, teachers’ readiness and resources. Therefore, the parties involved, such as teachers and administrators, should pay attention to these elements to reduce the risk of teachers’ task loads and also to meet the PPKI teachers’ job satisfaction in Johor.